Analysis of Promotion Strategies in Increasing The Number of New Students - Munarsih; Harsono, Yhonanda; Salami, Muhammad Musyfiq (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2025)
The author conducted this research at SDIT Bina Cendekia. The purpose of the study was to determine the promotion strategy for new student admissions during the pandemic. A qualitative approach is an analysis that is used without the use of numerical calculations, but based on judgments or opinions and the basics that can support subjective decision making. Data collection methods used in this study include observation, interviews and documentation obtained from the principal, teachers and staff of SDIT Bina Cendekia. The results of the study indicate that the marketing approach used in student recruitment at SDIT Bina Cendekia Depok is based on the concept of a promotional mix such as advertising including print media (signboards, banners, brochures), sales promotions that offer free registration fees, and personal sales based on. The school will also promote SDIT Bina Cendekia Depok to the surrounding community. Public relations/advertising, especially by contacting the nearest kindergarten to announce that SDIT Bina Cendekia Depok has started registering and direct sales, especially by providing brochures and other information so that prospective new students can get clearer information. The method is by providing the school's telephone number on the banner.